2011
DOI: 10.1364/oe.19.013722
|View full text |Cite
|
Sign up to set email alerts
|

Molecular orbital imaging via above-threshold ionization with circularly polarized pulses

Abstract: Above-threshold ionization (ATI) for aligned or orientated linear molecules by circularly polarized laser pulsed is investigated. It is found that the all-round structural information of the molecular orbital is extracted with only one shot by the circularly polarized probe pulse rather than with multi-shot detections in a linearly polarized case. The obtained photoelectron momentum spectrum directly depicts the symmetry and electron distribution of the occupied molecular orbital, which results from the strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…For instance, this HHG process offers an ideal framework for the study of strong-field dynamics [37]. Moreover, as the CPLP has already shown its great power in the application of (one-shot) imaging or structure detection of molecules [39][40][41][42], the HHG by CPLP can be potentially utilized for the imaging and detection of molecules with an all-optical method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, this HHG process offers an ideal framework for the study of strong-field dynamics [37]. Moreover, as the CPLP has already shown its great power in the application of (one-shot) imaging or structure detection of molecules [39][40][41][42], the HHG by CPLP can be potentially utilized for the imaging and detection of molecules with an all-optical method.…”
Section: Discussionmentioning
confidence: 99%
“…It is found that the higher efficiency is mainly contributed in the recombination step and is at least partly due to the higher recollision probability for molecules. Since this HHG process involves the unique recollision mechanism under a circularly polarized laser field, it will stimulate new potential applications, such as offering an ideal framework for study of strong-field dynamics [37] and (one-shot) imaging or structure detection of molecules with all optical methods [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, PMDs can be measured in a reaction microscope [22], where information on the molecular orientation is obtained by electron-ion coincidence. For molecular imaging, circularly polarized light effectively delivers a 360°scan of the aligned molecule [23][24][25], which is an advantage over linear polarization. In the classical trajectory model without Coulomb effects, electrons measured at an emission angle ϕ originate from ionization at the angle ϕ AE 90°with the sign depending on the rotation direction of the field.…”
mentioning
confidence: 99%
“…We use a 800 nm wavelength and a constant amplitude E 0 corresponding to an intensity of I ¼ 2.5 × 10 14 W=cm 2 , unless specified otherwise. Choosing a continuous wave (cw) field has the following reasons: (i) multicycle pulses avoid anisotropies introduced by the pulse envelope and thus bring out the angle-dependent ionization probability of the molecular orbital [24] and (ii) the cw field reduces the numerical workload.…”
mentioning
confidence: 99%
“…There are also other forms of polarizations, the circular and elliptical polarizations, which still involve abundant topics to be studied. Investigations on the PADs for both polar and non-polar molecules ionized by circularly polarized laser pulses have been performed lately [27,28,29], and very recently Abu-samha et al [30] has studied the photoelectron momentum distribution of atomic oribtals by elliptically polarized laser pulses. Nevertheless, investigations on the PADs in response to elliptically polarized exciting lasers especially from polar molecules are still in request.…”
Section: Introductionmentioning
confidence: 99%